Electromobility 2035: Economic and labour market effects through the electrification of powertrains in passenger cars - Anke Mönnig; Christian Schneemann; Enzo Weber; Gerd Zika; Robert Helmrich (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2019)
This study focuses on the economic effects of the phenomenon of the electrification of powertrains in passenger cars (e-mobility). The automotive industry is one of the leading sectors in Germany and the country is one of the world's leading car producers. Therefore the economic impact could be extensive. Using the scenario technique, a number of assumptions have been made and integrated into the QINFORGE analytical tool. At the beginning of the scenario, the underlying assumptions have a positive effect on the economic development. However, in the long run they lead to a lower GDP and level of employment. The change in technology will lead to 114,000 job cuts by the end of 2035. The economy as a whole will lose nearly 20 billion euros (0.6 % of the GDP). In the scenario, we assumed a share of only 23 percent of electric cars as compared to all new registered cars in 2035. The electrification of powertrains will have negative effects especially on skilled workers. The demand for specialist and expert activities will also decrease with a time delay. A much higher market penetration could lead to stronger economic effects. Furthermore, a higher market share of domestically produced cars and traction batteries could generate more positive economic effects. – – Dieser Beitrag untersucht für Deutschland die Wachstums- und Beschäftigungseffekte einer Elektrifizierung des Antriebsstrangs bei Personenkraftwagen (Pkw). Unter Zuhilfenahme der Szenarientechnik wurden eine Reihe von Annahmen getroffen und in das Analyseinstrument QINFORGE integriert. Die Ergebnisse weisen, im Vergleich zum Basisszenario, zwar zunächst einen positiven Wachstums- und Beschäftigungseffekt aus, langfristig muss aber mit einem niedrigeren Bruttoinlandsprodukts- und Beschäftigungsniveau gerechnet werden. Im Jahr 2035 werden ca. 114.000 Plätze aufgrund der Umstellung verloren gegangen sein. Die Gesamtwirtschaft wird bis 2035 einen Verlust in Höhe von 20 Mrd. EUR realisieren. Dies entspricht ca. 0,6 Prozent des preisbereinigten Bruttoinlandsproduktes. Von der Elektrifizierung des Antriebsstrangs werden vor allem Fachkräfte negativ betroffen sein. Zeitverzögert sinkt auch der Bedarf nach Spezialisten- und Expertentätigkeiten. Dabei wird von einem Elektroauto-Anteil an den Neuzulassungen von 23 Prozent bis 2035 ausgegangen, bei einer stärkeren Marktdurchdringung muss mit deutlich höheren Effekten gerechnet werden. Positive Wachstums- und Beschäftigungseffekt wären realisier bar, wenn Deutschland in der Lage wäre den Markt stärker mit inländisch produzierten Autos und produzierten Traktionsbatteriezellen zu versorgen.
Keywords: E17; E23; E24; E27; 330; electromobility; e-mobility; Germany; automotive industry; e-cars